2016
DOI: 10.1016/j.neuroimage.2015.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Entorhinal volume, aerobic fitness, and recognition memory in healthy young adults: A voxel-based morphometry study

Abstract: Converging evidence supports the hypothesis effects of aerobic exercise and environmental enrichment are beneficial for cognition, in particular for hippocampus-supported learning and memory. Recent work in humans suggests exercise training induces changes in hippocampal volume, but it is not known if aerobic exercise and fitness also impact the entorhinal cortex. In animal models, aerobic exercise increases expression of growth factors, including brain derived neurotrophic factor (BDNF). This exercise-enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 89 publications
(132 reference statements)
9
49
0
1
Order By: Relevance
“…Results of the current study extend findings of a negative association between CRF and cortical thickness to young adults and demonstrate that young adulthood is also a period in which enhanced CRF may benefit brain structure. Nevertheless, such findings may be region-specific, as a recent voxel-based morphometry study focusing on the medial temporal lobes observed a positive association between peak VO 2 and right entorhinal volume in young adults (Whiteman et al, 2016). Additional studies are needed to further delineate the relationship between CRF and brain structure in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the current study extend findings of a negative association between CRF and cortical thickness to young adults and demonstrate that young adulthood is also a period in which enhanced CRF may benefit brain structure. Nevertheless, such findings may be region-specific, as a recent voxel-based morphometry study focusing on the medial temporal lobes observed a positive association between peak VO 2 and right entorhinal volume in young adults (Whiteman et al, 2016). Additional studies are needed to further delineate the relationship between CRF and brain structure in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Th e same research group (Chaddock et al, 2010b) demonstrated through functional magnetic resonance a positive correlation between increased hippocampal volume and mnestic performance in pre-adolescent children who performed regular exercise (Alesi et al, 2015). Whiteman, Young, Budson, Stern and Schon (2016) further demonstrated how aerobic activity aff ects a particular area in the hippocampus called the entorhinal cortex. Researchers have shown that aerobic activity is related to an increase in grey matter in the entorhinal cortex, through which information travels.…”
Section: Physical Activity and Cognitive Processes: What Changes In "mentioning
confidence: 92%
“…Intervention studies show that aerobic training 3 days per week for at least 3 months to 1 year can prevent and/or reverse the age-related decline in hippocampal volume (Erickson et al 2011;Maass et al 2015; ten Brinke et al 2015). Interestingly, the exercise-induced increase in grey matter volume seems to occur in the hippocampus (Maass et al 2015; Duzel et al 2016), entorhinal (Whiteman et al 2016), and prefrontal cortex (Erickson et al 2014), with no change in the thalamus or caudate nucleus (Erickson et al 2011). …”
Section: Exercise and The Hippocampusmentioning
confidence: 99%